Efficacy of Oral Supplementation with Cholecalciferol Versus Calcifediol in Patients with Hypovitaminosis D After Stroke - Canneva, Stefania; De Giovanni, Anna; Pagella, Felicita; Pellegrino, Lucia; Iencinella, Francesco; Maestrini, Sara; Ponzano, Marta; Trompetto, Carlo; Mori, Laura (Nutrients, 2025)
Background/Objectives: Cholecalciferol and Calcifediol are commonly used for oral supplementation in patients with vitamin D deficiency. Several studies have compared these two molecules; however, the studied population has only included healthy postmenopausal women so far. This retrospective observational study aims to evaluate which molecule is more effective and faster in achieving serum 25(oh)D levels within the normal range in post-stroke patients during the subacute phase. Secondary aims include assessing potential differences in functional outcomes and investigating the possible correlation between the degree of hypovitaminosis D and stroke severity. Methods: We observed 85 in-patients who received either Cholecalciferol or Calcifediol during intensive rehabilitation. All subjects underwent functional evaluations, blood tests, and a bone densitometry (DEXA) scan. Results: Four months after starting supplementation, subjects receiving calcifediol achieved significantly higher 25(oh)D levels (p < 0.001) compared to those receiving cholecalciferol. No significant between-group differences were observed in secondary outcomes. Another key finding is that no statistically significant correlation was found between serum of 25(oh)D levels and stroke severity. Conclusions: These results highlight the importance of further investigating bone metabolism in post-stroke patients, though findings should be confirmed in larger studies.